Stability of Output Effects from Motor Cortex to Forelimb Muscles in Primates - Griffin, Darcy M. (Society for Neuroscience, 2009)
Stimulus-triggered averaging (StTA) of electromyographic (EMG) activity is a form of intracortical microstimulation that enables documentation in awake animals of the sign, magnitude, latency, and distribution of output effects from cortical and brainstem areas to motoneurons of different muscles. In this study, we show that the properties of effects in StTAs are stable and mostly independent of task conditions. StTAs of EMG activity from 24 forelimb muscles were collected from two male rhesus monkeys while they performed three tasks: (1) an isometric step tracking wrist task, (2) an isometric whole-arm push–pull task, and (3) a reach-to-grasp task. Layer V sites in primary motor cortex were identified and microstimuli were applied (15 μA) at a low rate (15 Hz). Our results show that the sign of effects (facilitation or suppression) in StTAs of EMG activity are remarkably stable in the presence of joint angle position changes (96% stable), whole-arm posture changes (97% stable), and across fundamentally different types of tasks such as arm push–pull versus reach-to-grasp (81% stable). Furthermore, comparing effects across different phases of a task also yielded remarkable stability (range, 84–96%). At different shoulder, elbow, and wrist angles, the magnitudes of effects in individual muscles were highly correlated. Our results demonstrate that M1 output effects obtained with StTA of EMG activity are highly stable across widely varying joint angles and motor tasks. This study further validates the use of StTA for mapping and other studies of cortical motor output.